SKARGA NA TWITTERZE (SPOSOBY WYRAŻANIA SKARG PRZEZ KLIENTÓW FIRM TELEKOMUNIKACYJNYCH) - Tereszkiewicz, Anna (Poradnik językowy, 2015)
This paper is dedicated to statements expressing complaint, which are published on Twitter, a microblogging website. The research material covers interaction between customers and service providers of telecommunication companies. The aim of the analysis is to determine the impact of the communication channel on the structure and content of the expressed complaints and to examine linguistic properties of complaints. The research serves also the purpose of identifying intentions of the users expressing their complaints and the degree of effectiveness of the complaints expressed on the social networking website. Taking up the analysis of the abovementioned problem is caused by increased frequency of using Twitter by enterprises and customers. The analysis enabled identifi cation of the most common components of the statements expressing complaint and the most popular linguistic devices aimed at expressing dissatisfaction.